Samobójstwo i zachowania ryzykowne młodzieży. Analiza zjawisk w świetle założeń biopsychoekologicznych - Formella, Zbigniew (Humaniora. Czasopismo Internetowe, 2020)
The above statement is of a well-known researcher of the subject of suicide. Suicide points to consider the phenomenon of various perspectives: philosophical, theological, sociological, clinical, psychological, and psycho-pedagogical. The choice of this direction of analysis depends on the theoretical and methodological assumptions adopted by the researcher. My study, focus on psycho-pedagogical. I will try to combine the phenomenon of suicide with the so-called “Young people with difficulties.” My analysis will be carried out in the area of bio-psycho-ecological theory, which allows me to approach this subject in a multidimensional way, because I am of the opinion of multidimensional approach brings the best results.